Evaluating the p53 as diagnostic marker by using liquid based cervical sample in cervical carcinogenesis - Zin, Anani Aila Mat (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2019)
Background: p53 is known as the guardian genome and tumour suppressor gene as it involved in the induction of cell cycles and preventing mutation by activating cellular apoptosis. P53 mutation is observed in numerous types of malignancies such as in ovary, lungs, breast, colorectal , uterus and cervical cancer. Cervical cancer is one of the most common cancer in the female population. According to the Malaysian National Cancer Registry 2007-2011, the prevalence of cervical cancer among other female cancer in Malaysia was observed at 7.7%. The association between the Human Papillomavirus (HPV) infection and cervical cancer is well established. The emergence of the HPV negative squamous lesion could hamper the high-risk HPV (hrHPV) detection in Pap smear. Instead of looking into the HPV protein, we explored the expression of p53 in various stages of cervical carcinogenesis and determine the utility of p53 as potential diagnostic marker for cervical cancer. Materials and Methods: This is a cross-sectional study using left over samples of routine liquid based cytology (LBP) from Ministry of Health facilities in Johor Bahru, Johor and Kota Bharu. Kelantan from May 2016 to May 2018. All the LBP samples were selected according to cervical carcinogenesis; negative for intraepithelial malignancy (NILM), low grade squamous intraepitheliallesion (LSIL}, high grade squamous intraepitheliallesion (HSIL} and squamous cell carcinoma (SCC) and fulfilled the inclusion and exclusion criterion. Each LBP smear underwent cytopathological examination by respective resident pathologists and certified medical laboratory technicians, results were classified according The Bethesda System (TBS) 2014. The selected left over samples were converted to cell blocks and were subjected for p53 IHC staining. The nuclear expression of p53 IHC stain was assessed and quantified by usingHisto-score (H-Score). The cytological diagnosis was not known during the interpretation of the IHC Result: The p53 IHC scores obtained showed an increase in p53 expression in more severe cervical dysplasia and SCC and showed good sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). The statistical analysis between the mean p53 IHC score with cervical carcinogenesis categories were done using analysis of variance (ANOVA) which showed statistically significant result, p value <0.05. Post-hoc test (Tukey) among the cervical carcinogenesis categories showed statistically significant results, p value <0.05. Conclusion: Our findings suggest that p53 can be used as a diagnostic tool to differentiate normal cervical pap smear samples from the sample that has undergone different stages of cervical carcinogenesis. p53 also manage to stratify each category of cervical carcinogenesis. The cell blocks are also providing an excellent ancillary test for routine cervical pap smears.